Semi-automated micromethod for estimating the unsaturated iron-binding capacity of serum using radioactive iron - Brozovich, B. (1969)
A semi-automated micromethod for the determination of the unsaturated iron-binding capacity (UIBC) of serum using radioactive iron and magnesium carbonate as an adsorbing substance is presented. The method has the advantage of simplicity and speed. The determination of UIBC is carried out on 0·1 ml of serum in duplicate, using autodiluters, at the rate of up to 200 sera per day. The reproducibility of the presented method is comparable to the reproducibility of other methods for the determination of iron-binding capacity. As the method is a simple one it can easily be introduced into laboratories with facilities for radioactive counting.